Prediksi Perkembangan Nilai Impor Komoditas Utama di Provinsi Sumatera Selatan Menggunakan C4.5 - Evi Purnamasari (Jurnal Informasi dan Teknologi, 2023)
Currently, our world is still being hit by the Covid-19 virus which has impacted society, experiencing a rapid decline in the economy. At present we are entering a market where the economy is very minimal, especially in the province of South Sumatra. This affects the import value of main commodities in South Sumatra Province. So in this study, researchers conducted trials in classifying matters related to cases of predicting the level of development of the value of imports of main commodities in South Sumatra Province. In this study, predictions will be made on the level of development of the value of imports of key commodities by applying the C4.5 method, so that they can be used as material for decision-making in building a more advanced government. Based on the results of the trial, the conclusion obtained is that as an importer, you should be wiser in determining the value of imports, especially if the wealth in our province is of greater interest to other countries. So far, the South Sumatra Province has a higher import value of fertilizer compared to other types of imports. This can be used in making a policy that is significant enough to be able to make the import value prices in the South Sumatra Province all high. Based on the trial results using the orange application, an accuracy of 96.15% was obtained, meaning it had an error rate of 13.85%. This shows from the results of testing using the Decision Tree that it is very good enough to be used in predicting the level of import value.